2022
DOI: 10.1002/ejic.202200260
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Assisted Synthesis of Y/ZSM‐5 Composite Zeolite and Its Application in Cracking Reaction

Abstract: Y/ZSM‐5 composite zeolite was synthesized by an aerosol assisted hydrothermal method including a two‐step crystallization. The aerosol technique was used to prepare the precursor of Y/ZSM‐5 composite zeolite. This helped to fully utilize the amorphous silica‐alumina species left in the primary crystallization solution of NaY zeolite, and to bring the two zeolites close to each other during the second crystallization step. The optimal adding sequence and synthesis conditions were investigated to reduce the amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Note that a high propylene yield is not indicative of deep cracking as it may simply reflect high 1,3,5‐TIPB conversion to diisopropylbenzene, whereas cumene and benzene yields are direct measures of deep cracking. Relationships between deep cracking and mesoporosity are previously discussed for zeolites [14,60] . Aghakhani et al showed that composites of amorphous aluminosilicate (ASA) and Y zeolite facilitated TIPB pre‐cracking during diffusion through a mesoporous ASA shell, with resulting DIPB isomers cracked to cumene and benzene over acid sites in the zeolite core [55] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that a high propylene yield is not indicative of deep cracking as it may simply reflect high 1,3,5‐TIPB conversion to diisopropylbenzene, whereas cumene and benzene yields are direct measures of deep cracking. Relationships between deep cracking and mesoporosity are previously discussed for zeolites [14,60] . Aghakhani et al showed that composites of amorphous aluminosilicate (ASA) and Y zeolite facilitated TIPB pre‐cracking during diffusion through a mesoporous ASA shell, with resulting DIPB isomers cracked to cumene and benzene over acid sites in the zeolite core [55] .…”
Section: Resultsmentioning
confidence: 99%
“…Relationships between deep cracking and mesoporosity are previously discussed for zeolites. [14,60] Aghakhani et al showed that composites of amorphous aluminosilicate (ASA) and Y zeolite facilitated TIPB pre-cracking during diffusion through a mesoporous ASA shell, with resulting DIPB isomers cracked to cumene and benzene over acid sites in the zeolite core. [55] Mesopores arising from acid-base treatments are also reported to increase the accessibility of strong Brønsted acid sites in ZSM-5, promoting TIPB conversion to deep cracking products (combined cumene and benzene selectivity of 23 % versus 18 % for untreated ZSM-5).…”
Section: Catalytic Cracking Of 135-tipbmentioning
confidence: 99%
“…Using the composite growth of two-phase zeolites, the adjustment of the acid type and acid strength of the catalyst can be achieved to a large extent; for example, through aerosolassisted hydrothermal synthesis, Zhao et al 6 produced Y/ ZSM-5 composite zeolites. Optimal addition sequences and synthesis conditions were also studied to reduce the template amounts and accelerate crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the catalytic performance of catalyst isomerization, the preparation of composite molecular sieve catalysts by different compounding methods has gradually attracted the attention of domestic and foreign researchers. Using the composite growth of two-phase zeolites, the adjustment of the acid type and acid strength of the catalyst can be achieved to a large extent; for example, through aerosol-assisted hydrothermal synthesis, Zhao et al produced Y/ZSM-5 composite zeolites. Optimal addition sequences and synthesis conditions were also studied to reduce the template amounts and accelerate crystallization.…”
Section: Introductionmentioning
confidence: 99%